FROM THE HISTORY OF FINANCIAL AND AGRICULTURAL INSTITUTIONS AND THEIR RESPONSIBILITIES IN TURKESTAN - U.Kh, Dzhumaev; S, Shodiev; F.K, Zhoniev; Yu.Yu, Safarov (International Journal of Psychosocial Rehabilitation, 2020)
--This article discusses the role of financial and economic institutions in the authoritarian system, along with the gradual establishment of the political dominance of the Russian Empire in Turkestan and its economic domination. This process was primarily associated with the introduction of colonial economic laws in Turkestan by the Russian Empire.It also analyzes on the basis of historical sources the important role of financial and economic activities among the functions of colonial administration. He called for the creation of more favorable economic conditions for Russian entrepreneurs, the bourgeoisie, officials; creation of state institutions dealing with finance, budget, taxes, credit and other areas; It is revealed that the famine is aimed at carrying out measures of police-economic significance aimed at preventing popular uprisings during the outbreak of the disease.